Adolescents as Game Designers: Developing New Literacies - Lacasa, Pilar; Cortés, Sara; García-Pernía, María (Transactions of the Digital Games Research Association, 2017)
The main goal of this paper is to analyse adolescent activities when designing video games in an innovative school environment based on affinity spaces. We analyse the development of digital literacies, understood as a critical understanding of the game in terms of its dimensions and the relationships between them, which contribute to turning it into a system. Methodologically speaking, the study relies on ethnography and action research. The project was carried out at a secondary school in Madrid, during the 2012-2013 academic year as an extracurricular programme. The participants were a group of twenty adolescents (14 girls and 6 boys) aged 14 to16, and their teacher. The members of the research team acted as participant observers. The analysis carried out was two-fold, considering firstly the tasks that took place over the course of time in relation to the adolescents' representations of the game, and secondly the products of these activities, which were present in the creation of the game. The results show that the students developed critical skills in relation to the game which are related to digital literacy.